Latino Adolescent Educational Affiliation Profiles. (November 2017) - Gonzalez, Laura M.; Cavanaugh, Alyson M.; Taylor, Laura K.; Stein, Gabriela L.; Mayton, Heather N.
Supporting postsecondary access for Latino adolescents is important due to the size of the population and mixed evidence of progress. In order to better understand the college-going and school belonging attitudes of Latinos, we used an exploratory latent profile analysis to identify the educational affiliation profiles present in a sample of Latino seventh- to 10th-grade students in the Southeastern United States. In addition, we investigated how proximal peer processes (support and discrimination) functioned to differentiate membership in the educational affiliation profiles. We found that a three-typology profile was the best fit to the data (low, moderate, and high educational affiliation), and that peer support was more likely to be associated with membership in the high profile (compared with low profile and moderate profile), while peer discrimination was more likely to be associated with membership in the moderate profile (as compared with the high profile). Implications for conceptualizing college readiness are offered.